A Study on Percutaneous Electrical Nerve Stimulation with Open Kinematic Exercises on Gluteus Medius Activation in Patellofemoral Pain Syndrome - Shunmathi, Saravanan; K., Kotteeswaran (INTI International University, 2023)
Background: Patellofemoral pain accounts for 25-40% of knee pain cases. It is thought that weakness or inadequate activation of gluteus medius muscle while weight-bearing can lead to internal rotation of the femur and consequently lateral tracking of the patella, gradually leading to patellofemoral pain syndrome. Percutaneous Electrical Nerve Stimulation is a novel treatment modality for the management of myofascial pain syndrome, when combined with open kinematic exercises, it helps to improve the strength of a particular muscle. Objective: To determine the effects of Percutaneous Electrical Nerve Stimulation with open kinematic exercises on gluteus medius activation in patellofemoral pain syndrome. Methods: A study conducted on 30 patients with patellofemoral pain syndrome. All the patients received Percutaneous Electrical Nerve Stimulation, in the myofascial trigger points of the gluteus medius muscle, along with it open kinematic exercises were given targeting the gluteus medius muscle. PENS was given twice a week for 6 weeks. Open kinematic exercises were given 5 days a week for 6 weeks. Results: Paired t – test was used to analyze the statistical difference. The pre - test value of electromyography was (138.11 ± 2.08, P ˂ 0.0001) and post - test value was (140.61 ± 1.83, P ˂ 0.0001). As for the pain score (NPRS) the pre – test value was (6.67 ± 1.54, P ˂ 0.0001) and post - test value was (3.2 ± 1.2, P ˂ 0.0001). A significant difference was noted in the gluteus medius activation levels and the pain score with the application of Percutaneous Electrical Nerve Stimulation with open kinematic exercises targeting the gluteus medius muscle. Conclusion: The study concluded that Percutaneous Electrical Nerve Stimulation with open kinematic exercises is effective in the activation of gluteus medius muscle.